Effect of age and season on the Epididymal Sperm and testosterone level in camel (camelus dromedarius): Ali A. Abd@ and Najlaa S. Ibrahim - Abd, Ali A. (The Iraqi Journal of Veterinary Medicine, 2014)
The aim of this study was to evaluate the effect of age and season on the epididymal sperm and level of testosterone in camel. A total 103 camel testes samples were collected from Al-Najaf slaughter house during a cold season (December 2012, January and February 2013) and moderatehot season (March, April and May, 2013). Testes were divided into 3 Gs according to camel age, G1 included the testes of 2-3years, G 2 (3 – 4years) and over 4 years (G 3). Blood samples were collected for determination of serum testosterone level. The sperms were obtained from the tail of epididymis from all animals groups and the results of the sperms individual motility percentage was increased at the level of (P< 0.05) significantly with age progress in both seasons. Also, sperm motility of G3 recorded a significantly higher than those of G1 and G2 in cold and moderate-hot seasons .The live percentage of G 3 animals was 90.01% in cold season with a significantly higher than those of other Gs and in both seasons. However, the live sperm percentage of G 3 during moderate-hot season was 87.82% and G 2 during moderate-hot and cold seasons were 88.58 and 88.72% respectively, showed significantly higher than those of G1 during cold and moderate-hot seasons .The concentration of sperm obtained from epididymis tail of bulls camel significantly increase with age progress in both seasons. However, the mean of the sperm concentration in cold season showed significance higher than those in moderate-hot season in animals of G 1 and 3, respectively. The abnormal morphologically sperm percentage of animals G 1 in both cold and moderate-hot seasons were significantly higher than those of G3.The testosterone levels of the young animals (under 4 years) increased gradually and reached its peak in February 2.28 ng/ml and March 2.27ng/ml. In the same trend older animal (more than 4 years) was showed 8.14 and 7.35 ng/ml, respectively. The older animals showed a significantly monthly, higher values than those of the younger animals in their testosterone level started from January up to May. In conclusions during cold months the camel over 4 years shows higher percentage of epididymal sperms parameters (live and individual motility) and sperms concentration as well as serum testosterone level.